Ultrasound-Guided Platelet-Rich Plasma Treatment: Application and Technique - Lee, Kenneth S. (Seminars in Musculoskeletal Radiology, 2016)
Platelet-rich plasma injection is a minimally invasive treatment method for common overuse tendon injuries. This article discusses the biology of platelet-rich plasma (PRP), the healing cascade that PRP promotes, and how PRP composition may differ depending on centrifuge method. It also highlights the common uses of PRP tendon injection and offers an update on the most current clinical evidence-based literature.
Keywords: platelet-rich plasma; PRP; tendinopathy; tendon